Corporate governance, intellectual capital, sustainability initiative and performance of medium size firms in Nigeria - Samuel, Adedeji Babatunji (2020)
Even though medium-sized firms are involved in job generation, contributions to Gross Domestic Product, and exports of an economy, most new firms close down before their fifth birthday, thus, further exacerbating the performance trials. The circumstances as above are traceable to the factors of bad governance, low intellectual power, lack of sustainability strategies, little financial capacity, and capabilities, as well as inadequate provision of infrastructure and enabling environments by the various governments. Thus, this study examines the relationship between corporate governance, intellectual capital, sustainability initiative, and firms' performance (financial and non-financial) of medium-sized firms in Nigeria. It also determines the perceptions of the business executives as to whether sustainability initiative mediates the relationships among corporate governance, intellectual capital, and firms' performance of medium-sized firms in Nigeria. The study adopts the cross-sectional survey and multi-stage sampling method with data collected through a three hundred (300) structured questionnaire. The analysis of the data is via the Partial Least Square Structural Equation Modeling (PLS-SEM). Overall, the results of this study indicate a clear fact that the principles of corporate governance are relevant to medium-sized firms. At the same time, those of intellectual capital requires the attention of the boards and management of firms for recognition and application. The results showed that corporate governance and sustainability initiative has a significant relationship with financial performance. In contrast, intellectual capital has an insignificant relationship with financial performance and non-financial performance. Furthermore, corporate governance has a significant positive relationship between non-financial performance and sustainability initiative. Intellectual capital has a significant influence on sustainability initiative, but intellectual capital has an insignificant relationship with non-financial performance. Also, there is a significant mediating effects of a sustainability initiative in the relationship between corporate governance and intellectual capital with financial performance. In contrast, those of corporate governance and intellectual capital with non-financial performance do not have any significant effects. The outcomes produced in this study are in agreement with the theories, which include the stakeholder theory, institutional theory, and agency theory. There is no substantial relevance concerning the resource-based view theory. Thus, the theoretical support justifies the design and application of corporate governance codes for medium-sized firms and replication of the laws by other developing countries. Again, more training is required to inform the workforce, management, and boards on the benefits of focusing more on the intellectual capital dimensions to improve the productivity of firms. Theoretically, the mediation effect of sustainability initiative on the relationship between corporate governance, and intellectual capital with financial performance is an addition to the existing body of literature. The study shows that even though there is a significant relationship between corporate governance and firm performance, the medium-sized firms lack corporate governance codes required for evaluating performance. Also, non-financial performance indices provide support for the evaluation of firms. Besides, the study deviates from the regular review of large and listed firms to the medium-sized firms to give effect to the evaluation of firm size. Limitations of the study include non-application of a longitudinal approach for the research and the non-inclusion of moderating variables such as the age of the firm, industry, age of the workforce, etc. The cultural and religious aspects do not receive consideration. Future studies are to cover comparative research on issues such as the extent of compliance with corporate governance codes between listed firms and medium-sized firms and especially those that concern nonfinancial indicators in other countries on the continent of Africa and other developed nations. The policymakers can look in the direction of instituting combined corporate governance codes to cover the activities of both the listed and medium-sized firms, as is the practice in other advanced countries of Europe and Australia. On the other side, since the focus is on the social initiatives by the medium-sized firms, researchers need to determine and encourage studies in the area of environmental initiatives by medium-sized firms. Also, the aspect of spiritual capital requires further investigation by both listed and medium-sized firms in the developed and developing economies to enhance its relevance as a dimension of intellectual capital.